New species of small scaly crickets of genus Micrornebius (Orthoptera: Mogoplistidae; Mogoplistinae) from Singapore - Tan, Ming Kai (Zootaxa, 2014)
The small and cryptic scaly crickets of the genus Micrornebius from Singapore are reviewed. The Henningian species concept was applied and morphology was used to estimate species boundaries. Three new species are described: Micrornebius distinctus sp. n., Micrornebius eclipsus sp. n. and Micrornebius mandai sp. n. This increases the number of species Micrornebius from Singapore to five. A tentative key to the species of Micrornebius from Singapore is provided.